Restorative Justice for Online Hate Speech: A Socio-Legal Framework - Arda, Ravi; Christian, Deva; Raga, Wirawan Jati (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
This study explores the development of a socio-legal framework for restorative justice (RJ) as an alternative approach to addressing online hate speech in Indonesia. In light of the increasing limitations of retributive legal systems—especially in digital contexts—this research investigates how RJ principles can be applied to digital conflict resolution involving victims, offenders, digital communities, and legal institutions. Using a qualitative descriptive design and a socio-legal lens, data were collected through semi-structured interviews, document analysis, and online observation. Findings reveal a substantial gap between formal punitive mechanisms and the social realities of online interaction. While legal actors tend to adopt retributive responses, digital communities have shown greater alignment with restorative practices, including public apologies, dialogue, and empathy.Four major themes rose to the fore: institutional resistance, psychosocial needs of the victims, grassroots initiatives for restorative justice, and the place of ethical technology in that regard. The most important outcome is an approved Socio-Legal Restorative Justice Digital Framework, which synergistically combines normative legal knowledge, community knowledge, and digital mediation tools. The framework theoretically and practically relates to a socio-juridical lexicon for promoting inclusive, participatory, and transformative justice in cyberspace, with an avenue for implementing and evolving adaptive policy in the future.